2022
DOI: 10.3390/healthcare10091777
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Evidence-Informed Solution to Emotional Distress in Public Safety Personnel and Healthcare Workers: The Social Support, Tracking Distress, Education, and Discussion CommunitY (STEADY) Program

Abstract: Public safety personnel (PSP) and healthcare workers (HCWs) are frequently exposed to traumatic events and experience an increased rate of adverse mental health outcomes compared to the public. Some organizations have implemented wellness programming to mitigate this issue. To our knowledge, no programs were developed collaboratively by researchers and knowledge users considering knowledge translation and implementation science frameworks to include all evidence-informed elements of posttraumatic stress preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…It may also be useful to develop prevention strategies that allow HCWs to process the stressors as they are occurring with their colleagues and supervisors. Specifically, they may benefit from peer partnering, distress tracking, psychoeducation, peer support groups, psychological debriefing, and community building activities, which have been proposed as interventions that should be tested high stress work settings ( Ellis and Korman, 2022 ). As suggested by our group and others ( Guastello et al, 2022 ; Meredith et al, 2022 ), engagement of healthcare leadership in assessing and improving working conditions, and increasing communication and integration across systems can improve both employee engagement and sense of professional fulfillment/accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be useful to develop prevention strategies that allow HCWs to process the stressors as they are occurring with their colleagues and supervisors. Specifically, they may benefit from peer partnering, distress tracking, psychoeducation, peer support groups, psychological debriefing, and community building activities, which have been proposed as interventions that should be tested high stress work settings ( Ellis and Korman, 2022 ). As suggested by our group and others ( Guastello et al, 2022 ; Meredith et al, 2022 ), engagement of healthcare leadership in assessing and improving working conditions, and increasing communication and integration across systems can improve both employee engagement and sense of professional fulfillment/accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…We previously amalgamated validated questionnaires of mediators of PTSI, anxiety, depression, and quality of work life (described in [ 23 ]) to make up the “Wellness Assessment” for the Tracking Distress (T) part of STEADY. Considering the many competing demands faced by HCWs and limited time available, we were asked to create a brief version to help elucidate organizational needs (which could then be used for the distress tracking component of STEADY).…”
Section: Step 2: Planning Steady Implementation (At the Organizationa...mentioning
confidence: 99%
“…Our team spent approximately three years prior to the COVID-19 pandemic developing the evidence-informed Social Support, Tracking Distress, Education And Discussion, communitY (STEADY) program, completing the Knowledge Creation component of the KTA framework [ Figure 1 ]. Literature review on the topic, program development and description of the program are reported elsewhere [ 23 ]. Briefly, STEADY targets evidence-informed mediators of PTSI and resilience in first responder and healthcare worker populations (social support, earlier intervention for distress, substance use, stigma, and burnout).…”
Section: Introductionmentioning
confidence: 99%